Modeling of plastic deformation of porous powder materials - Zayats, G.; Kusin, R.; Kapcevich, V. (Mathematical Modelling and Analysis, 2003)
In the present study the model of plastic deformation of porous powder materials (PPM) is described and numerically simulated. This model enables prediction of change of fundamental technological parameters of PPM in plastic deformation conditions, i.e. porosity, pore size, specific surface and mechanical properties. Porous media is described by unit cells consisting of eight powder particles. The parameters of unit cell (the distance between the centers of particles, the angles of the array and the dimensions of interparticle connections) form the model of porous material and define its technological characteristics. The model takes into account the effect of deforming anisotropy on PPM properties. Calculations are performed in nonorthogonal coordinates connected with unit cell. In the case of uniaxial straining obtained numerical results have shown good agreement with the experimental results.Plastiškų deformacijų modeliavimas poringose miltelių medžiagoseSantrauka. Šiame darbe aprašomos ir nagrinėjamos plastiškos poringų miltelių medžiagos (PPM) deformacijos, atliekamas skaitinis jų modeliavimas. Šis modelis leidžia prognozuoti PPM technologinių parametrų kitimą plastiniu deformacijų savybėse. Poringosios medžiagos vienetinė ląstelė aprašoma aštuoniomis miltelių dalelėmis. Šios vienos medžiagos ląsteles parametrai formuoja poringosios terpės modelį ir apibrėžia jo technologines charakteristikas. Į šį modeli įtraukti PPM savybių neizotropiniai efektai. Skaičiavimai atlikti neortogonalioje koordinačių sistemoje susietoje su vienetine ląstele. Gauti skaitiniai rezultatai neašinėms įtampoms rodo gerą atitikimą eksperimentiniams matavimams.First Published Online: 14 Oct 2010